INTEGRATING QUANTUM LEARNING TO IMPROVE STUDENTS’ LINGUISTIC COMPETENCE - Handayani, Nengah Dwi; Widiastuti, Ida Ayu Made Sri (Denpasar Institute, 2019)
Quantum Learning is a trend of meaningful learning that allows the creation of a fun learning atmosphere. Motivation and students' engagement become a prime attraction for successful teaching and learning practices. Happiness in learning provides a positive impact on students’ peacefulness and builds up students’ creativity. The present study was conducted to attempt at improving linguistic competence through implementing quantum learning to EFL students triggered by the fact that the students have poor ability in linguistic competence. The results of the analysis of the questionnaire clearly showed that the students’ attitudes and motivation in learning linguistic competence through quantum learning were improved significantly. This study implies that quantum learning is an effective teaching model to improve the students’ linguistic competence, Therefore, the use of quantum learning should be carefully considered as an effort to optimally maximize students' engagement in language learning.